Optical-feedback Semiconductor Laser Michelson Interferometer - Rodrigo, Peter John; Lim, May; Saloma, Caesar (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
An optical-feedback semiconductor laser Michelson interferometer (OSMI) is presented for measuring microscopic linear displacements without ambiguity in the direction of motion. The two waves from the interferometer arms, one from the reference mirror and the other from the reflecting moving target, are fed back to the lasing medium (λ = 830 nm), causing variations in the laser output power. We model the OSMI into an equivalent Fabry-Perot resonator and derive the dependence of output power on path difference between the two interferometer arms. Numerical and experimental results obtain output power that varies periodically (period = λ/2) with path difference. The output power variation exhibits an asymmetric behavior with the direction of motion, which is utilized to measure the amplitude of vibration of (1) a piezoelectric transducer (PZT) and (2) an audio speaker with directional discrimination.